Study of the properties of monolithic concrete of large open surface modular flat structures in dry hot climates and acceleration of hardening - M.S. Egamberdiev (Peerian Journals Publishing, 2022)
The optimal ... design was determined ... from the condition of ensuring its maximum strength, including a layer of dry concrete mix. To obtain the objectivity of the characteristics, taking into account the total thickness of the structure and the ratio of the heights of the layer of dry and mixed concrete, the method of mathematical planning of the experiment was applied. An analysis of the data obtained will make it possible to establish that there is such a layer thickness of the dry concrete mix at which the overall strength of the structures corresponds to the design and even exceeds it. The decision ... made it possible to conclude that high .. layer contact can be obtained with a ratio of b / N = 65 ... 72% or a dry layer thickness of 3 ... 6 cm. was evaluated in experiments with concretes of three different compositions (c1, c2, c3) placed by the dosage of components, cement content, ... ratio and perversity at 28 days of age. These compositions are used for the most common types of extended structures. An increase in the proportion of cement in concrete leads to an increase
Keywords: monolit; concrete; layer; climate